2018
DOI: 10.1111/febs.14393
|View full text |Cite
|
Sign up to set email alerts
|

The role of glucocerebrosidase in Parkinson disease pathogenesis

Abstract: GBA encodes the lysosomal enzyme glucocerebrosidase (GCase), an enzyme involved in sphingolipid metabolism. Mutations in the GBA gene are numerically the most important risk factor for developing Parkinson disease (PD) accounting for at least 5% of all PD cases. Furthermore, loss of GCase activity is found in sporadic PD brains. Lysosomal dysfunction is thought to play a principal role in PD pathogenesis and in particular its effect on the metabolism of α-synuclein. A hallmark of PD is the presence of intraneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 135 publications
(238 reference statements)
4
81
0
Order By: Relevance
“…Multiple studies have established a link between mutations in GBA1 and PD (Gegg & Schapira, 2018;Lesage et al, 2011;Sidransky et al, 2009;Winder-Rhodes et al, 2013). Although underlying mechanisms and pathways have been pursued, the basis for this association is not fully understood.…”
Section: Parkinson Diseasementioning
confidence: 99%
“…Multiple studies have established a link between mutations in GBA1 and PD (Gegg & Schapira, 2018;Lesage et al, 2011;Sidransky et al, 2009;Winder-Rhodes et al, 2013). Although underlying mechanisms and pathways have been pursued, the basis for this association is not fully understood.…”
Section: Parkinson Diseasementioning
confidence: 99%
“…Whereas homozygous GBA mutation cause Gaucher disease (GD), GBA heterozygosity is a potential risk factor for developing PD with an earlier age of onset and a major risk to develop dementia compared to idiopathic PD [17]. Moreover, recent studies showed that GBA heterozygous mutation is linked with dysfunction in mitophagy [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous mutations in progranulin cause NCL (Smith, Damiano, et al, 2012) Null mutation in GRN gene decreases the release of exosomes (Benussi et al, 2016) Gaucher disease GBA GBA encodes beta-glucosidase, a lysosomal enzyme. GBA mutations also increase the risk to PD (Gegg & Schapira, 2018) Undetermined TA B L E 1 (Continued) of CAG nucleotide repeats in the gene huntingtin. The number of CAG repeats determines the median age of onset, ranging from 27 to 66 years (Brinkman, Mezei, Theilmann, Almqvist, & Hayden, 1997).…”
Section: )mentioning
confidence: 99%